JPTCP 2023
DOI: 10.47750/jptcp.2023.30.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Spike Protein of SARS-CoV2 from (Merremia mammosa (Lour) Hall. F.) Bioactive Compounds: Molecular Docking and ADMET Study

Abstract: Spike protein is a receptor protein that has e role in the entry step of SARS-CoV2. This protein will bind to the ACE2 receptor in the human body and activate TMPRSS2. Inhibition of this protein will prevent the binding of the virus to host cells to spread the infection. This study aims to identify the activity of bioactive compounds of Merremia mammosa (Lour) tuber obtained from LC-MS/MS QTOF analysis of a previous study against the Spike protein of SARS-CoV2 using molecular docking and ADMET analysis. Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Merremia mammosa Hall was found to have action in suppressing the spike protein of SARS-CoV2 with the PDB id. 6M0J protein, as determined by an in silico investigation of the chemical analysis using LC-MS/MS QTOF [11]. The cytotoxic test with Vero E6 cells (host of the SARS-CoV2 virus) from the ethanol extract of bidara upas using the MTT method showed that the maximum non-toxic concentration (MNTC) is 500 µg/mL, as determined as the maximum concentration of the extract at which the cells developed normally, therefore the viral inhibition assay used 500 µg/mL as highest concentration [18,19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Merremia mammosa Hall was found to have action in suppressing the spike protein of SARS-CoV2 with the PDB id. 6M0J protein, as determined by an in silico investigation of the chemical analysis using LC-MS/MS QTOF [11]. The cytotoxic test with Vero E6 cells (host of the SARS-CoV2 virus) from the ethanol extract of bidara upas using the MTT method showed that the maximum non-toxic concentration (MNTC) is 500 µg/mL, as determined as the maximum concentration of the extract at which the cells developed normally, therefore the viral inhibition assay used 500 µg/mL as highest concentration [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the results of the plaque test showed that the higher the concentration given, the % inhibition increased, which means that the cell death zone was getting bigger. This activity is because Merremia mammosa Hall contains Gemixanthone A which provides inhibiting activities to SARS-COV2 Spike Protein [11]. Agil et al [29], examined the rhizome of the bidara upas used for research as an antituberculosis drug by the Madurese community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian terbaru yang dilakukan oleh Purwitasari dkk., (2023) menjelaskan bahwa senyawa flavonoid menunjukkan aktivitas penghambatan yang baik terhadap protein spike SARS-COV-2 [19]. Diantara senyawa flavonoid yang terkenal memiliki berbagai manfaat farmakologi seperti antiinflamasi, antiosteoporosis, neurodegeneratif adalah Genistein, Daidzein, Glycitein, Formonoetin, dan Biochanin A [20,21].…”
Section: Pendahuluanunclassified